2021
DOI: 10.3389/fvets.2021.702018
|View full text |Cite
|
Sign up to set email alerts
|

An Accessible Alternative to Melarsomine: “Moxi-Doxy” for Treatment of Adult Heartworm Infection in Dogs

Abstract: Canine heartworm infection, caused by the filarial parasite Dirofilaria immitis, represents a serious and expanding animal welfare concern that is expected to increase due to the effects of climate change and the COVID-19 pandemic. A body of evidence has emerged to support the use of a non-arsenical adulticide treatment protocol, using moxidectin and doxycycline to kill adult heartworms over a prolonged period. While a three-dose protocol using the arsenical drug melarsomine is currently the safest and most ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 100 publications
(266 reference statements)
0
12
0
Order By: Relevance
“…According to [ 28 ], even though melarsomine is still widely used by veterinary practitioners in Italy, a monthly macrocyclic lactone together with doxycycline is currently being used by over 30% of surveyed veterinary facilities. The use of moxidectin is a valid alternative to ivermectin, as shown by several studies [ 8 10 , 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [ 28 ], even though melarsomine is still widely used by veterinary practitioners in Italy, a monthly macrocyclic lactone together with doxycycline is currently being used by over 30% of surveyed veterinary facilities. The use of moxidectin is a valid alternative to ivermectin, as shown by several studies [ 8 10 , 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the combination of moxidectin/ doxycycline has superior adulticide efficacy compared to ivermectin/doxycycline [17]. Grandi et al [5] reported 73% efficacy 10 months after the beginning of doxycycline (daily for 1 month) combined with oral ivermectin every 15 days for 6 months.…”
mentioning
confidence: 99%
“…The use of doxycycline at 10 mg/kg PO SID, rather than BID, in the current THS protocol was based on lack of consensus between expert guidelines, absence of studies demonstrating superiority of BID dosing, cost advantages of less frequent dosing, and concerns about GI adverse effects [19]. In one study, doxycycline 10 mg/kg BID was superior to SID dosing, as measured by residual micro larial Wolbachia DNA [14], but negative PCR or antibody tests may not be a necessary end-point for effective clinical reduction of the pro-in ammatory effects of Wolbachia.…”
Section: Discussionmentioning
confidence: 99%
“…This impact is even greater for organizations operating in endemic areas, where a high percentage of dogs may be infected. Additionally, a prolonged period of exercise restriction during HW treatment is of particular concern for shelter dogs [19], which are already subject to chronic stress [20] and for whom exercise may be the most available and practical form of enrichment. Placing dogs with HWI in foster homes for the duration of their treatment is ideal, but not always feasible.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the combination of moxidectin/doxycycline has superior adulticide e cacy compared to ivermectin/doxycycline [17]. Grandi et al [5] reported 73% e cacy 10 months after the beginning of doxycycline (daily for 1 month) combined with oral ivermectin every 15 days for 6 months.…”
Section: Introductionmentioning
confidence: 99%